Вариационный подход к решению обратной задачи при накоплении сейсмических сигналов в активном мониторинге - Мостовой, В.С.; Мостовой, С.В. (Видавничий дім "Академперіодика" НАН України, 2008)
In the approach to the solution of ill-posed problems such as the integral equations of convolution, it is important to construct such procedures of the solution which would be based on the additional information specifying a model and lead to a stable solution. These equations are a good model for a wide range of phenomena and are widely used in geophysics. Such an approach in the form of an estimation of these parameters by the chosen criterion is offered. It is based on the use of a priori distributions of free parameters of the model. The numerical example is given.